2013
DOI: 10.1038/bjc.2013.733
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of a nurse-led psychosocial intervention on health-related quality of life in patients with head and neck cancer: a randomised controlled trial

Abstract: Background:Head and neck cancer (HNC) patients are prone to have a poor health-related quality of life after cancer treatment. This study investigated the effect of the nurse counselling and after intervention (NUCAI) on the health-related quality of life and depressive symptoms of HNC patients between 12 and 24 months after cancer treatment.Methods:Two hundred and five HNC patients were randomly allocated to NUCAI (N=103) or usual care (N=102). The 12-month nurse-led NUCAI is problem-focused and patient-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 35 publications
1
69
1
1
Order By: Relevance
“…According to a person-centred approach [10], this team should also include the patient with HNC working in partnership with the healthcare personnel. Our person-centred intervention was coordinated by oncology nurses, which is in line with several previous projects addressing not only the needs in this patient group [8, 32, 33] but also the formation of such a multidisciplinary team. Using nurses to coordinate the project should result in acceptable costs for the intervention, and their general interest in this type of follow-up has been described previously [32, 34].…”
Section: Discussionmentioning
confidence: 71%
“…According to a person-centred approach [10], this team should also include the patient with HNC working in partnership with the healthcare personnel. Our person-centred intervention was coordinated by oncology nurses, which is in line with several previous projects addressing not only the needs in this patient group [8, 32, 33] but also the formation of such a multidisciplinary team. Using nurses to coordinate the project should result in acceptable costs for the intervention, and their general interest in this type of follow-up has been described previously [32, 34].…”
Section: Discussionmentioning
confidence: 71%
“…) and supportive care (Van der Meulen et al . ) after treatment evaluate interventions that are provided in addition to medical follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Depression symptoms remained significantly lower at 18 months post-diagnosis for patients who received the intervention and were lower, but no longer significantly so, at 24 months (van der Meulen et al, 2014). Importantly, this intervention was also associated with significant improvements in HRQOL (emotional functioning) at 12-, 18-, and 24-months post-diagnosis, and with decreased pain, fewer problems swallowing, and improved mouth-opening abilities at 12 and 18 months (van der Meulen et al, 2014). It is noteworthy that the intervention was associated with improvements in an array of emotional, physical, and functional symptoms, including depressive symptoms, pain, HRQOL, and successful swallowing and mouth openingfactors that the present study identified as important predictors of the trajectory of weight loss.…”
Section: Discussionmentioning
confidence: 86%
“…Depression symptoms remained significantly lower at 18 months post-diagnosis for patients who received the intervention and were lower, but no longer significantly so, at 24 months (van der Meulen et al, 2014). Importantly, this intervention was also associated with significant improvements in HRQOL (emotional functioning) at 12-, 18-, and 24-months post-diagnosis, and with decreased pain, fewer problems swallowing, and improved mouth-opening abilities at 12 and 18 months (van der Meulen et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation